2002
DOI: 10.1177/152660280200900105
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Thrombin Injection of Carotid Artery Pseudoaneurysm

Abstract: Percutaneous thrombin injection may be a new and successful method of treating carotid artery pseudoaneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Carotid PSA is a rare complication of CEA, as is PSA after inadvertent puncture during attempted placement of central venous catheters. 2,3 In this patient, the PSA may have been associated with the patient's increased risk of bleeding, due to continued use of aspirin, clopidogrel, and heparin for myocardial infarction which developed immediately after the CEA. The patient was on aspirin therapy during the CEA, which is a common challenge for us while performing this procedure.…”
Section: Discussionmentioning
confidence: 94%
“…Carotid PSA is a rare complication of CEA, as is PSA after inadvertent puncture during attempted placement of central venous catheters. 2,3 In this patient, the PSA may have been associated with the patient's increased risk of bleeding, due to continued use of aspirin, clopidogrel, and heparin for myocardial infarction which developed immediately after the CEA. The patient was on aspirin therapy during the CEA, which is a common challenge for us while performing this procedure.…”
Section: Discussionmentioning
confidence: 94%
“…Only one case of ICA PSA successfully treated with this technique has been reported but in an adult patient [13]. The benefits of this technique are many (e.g., lack of use of foreign material and unaltered flow of the affected ICA) and far outweigh the risks (e.g., intra-arterial migration).…”
Section: Discussionmentioning
confidence: 95%
“… 5 Furthermore, the addition of coil embolization with coils being placed directly into the PA and stenting across the native carotid artery has also been reported with success. 5 Holder et al reported injecting thrombin directly into the PA with successful obliteration of a traumatic PA. 6 Multiple, overlapping stents have also been reported in treatment of carotid PA, after endarterectomy and for traumatic PA. 4 7 Benndorf et al reported an overlapping covered stent technique for treatment of a dissecting traumatic carotid PA with adequate obliteration. 7 …”
Section: Discussionmentioning
confidence: 99%